Genome-wide association study for growth traits with 1066 individuals in largemouth bass (Micropterus salmoides) - Han, Wei; Qi, Ming; Ye, Kun; He, Qiwei; Yekefenhazi, Dinaer; Xu, Dongdong; Han, Fang; Li, Wanbo (Frontiers in Molecular Biosciences, 2024)
The largemouth bass is a native species of North America that was first introduced to mainland China in the 1980s. In recent years, it has been extensively farmed in China due to its high meat quality and broad adaptability. In this study, we collected growth trait data from 1,066 largemouth bass individuals across two populations. We generated an average of approximately 7× sequencing coverage for these fish using Illumina sequencers. From the samples, we identified 2,695,687 SNPs and retained 1,809,116 SNPs for further analysis after filtering. To estimate the number of genomewide effective SNPs, we performed LD pruning with PLINK software and identified 77,935 SNPs. Our GWAS revealed 15 SNPs associated with six growth traits. We identified a total of 24 genes related to growth, with three genes-igf1, myf5, and myf6-directly associated with skeletal muscle development and growth, located near the leading SNP on chromosome 23. Other candidate genes are involved in the development of tissues and organs or other physiological processes. These findings provide a valuable set of SNPs and genes that could be useful for genetic breeding programs aimed at enhancing growth in largemouth bass.